Analysis of Long-Term Contraception in Women of Childbearing Age on Mekarbakti Panongan Village Tangerang Regency in 2022 - Azizah, Iza Siti; Azzahroh, Putri; Rukmaini (Rajaki of Tulip Medika Publisher, 2023)
Background: One of the government's programs in family planning is the improvement of family planning services with long term contraception, but this was still hampered due to the high use of non-longterm contraception in Indonesia. Based on data from the Indonesian Ministry of Health, especially in Banten, it also shows that there is still a high use of non- long term contraception compared to long term contraception. The purpose of the study was to determine the relationship between age, occupation, knowledge, information on family planning services, husband support, culture, and attitudes of FAC women with the use of longterm contraception. Purpose: This study aims to determine factors related with long-term contraceptive use on Mekarbakti Panongan sub-district, Tangerang Regency, Banten Province, in 2022. Methods: The method used an analytical survey with a cross-sectional approach. The population in this study was all acceptors recorded in the family planning register located in the working area of Mekarbakti Panongan Village, Tangerang, who use long term contraception and those who do not use long term contraception, which is 1,984 acceptors. Sampling using accidental sampling, where 96 samples were obtained. Results: Chi-square test results (0.05) for age sig-p value 0.050, work sig-p value 0.892, knowledge sig-p value 0.000, information by health workers sig-p value 0.014, husband support sig-p value 0.038, culture sig-p value 0.005, and attitude sig-p value 0.062. Conclusion: In this study, there was an influence of age, knowledge, information provided by health workers, husband support, and culture on the selection of long term contraception, while occupational factors and attitudes did not have an influence on the selection of long term contraception.